Numerical investigation of energy loss distribution in the cavitating wake flow around a cylinder using entropy production method - Zhang, Guangjian; Yang, Xiufei; Li, Yan; Ge, Mingming; Gu, Fadong (Frontiers in Energy Research, 2023)
The wake flow of a circular cylinder is numerically investigated by Large Eddy Simulation (LES) combined with the Schnerr-Sauer cavitation model. By comparing entropy production in the presence or absence of cavitation, the energy loss distribution in the wake flow field of a cylinder is explored, shedding light on the interactions between multiscale vortex systems and cavitation. The comparative results reveal that, under non-cavitating conditions, the energy loss region in the near-wake area is more concentrated and relatively larger. Energy dissipation in the wake flow field occurs in regions characterized by very high velocity gradients, primarily near the upper and lower surfaces of the cylinder near the leading edge. The influence of cavitation bubbles on entropy production is predominantly observed in the trailing-edge region (W1) and the near-wake region (W2). The distribution trends of wall entropy production on the cylinder's surface are generally consistent in both conditions, with wall entropy production primarily concentrated in regions exhibiting high velocity gradients.